2009
DOI: 10.1093/ejechocard/jen183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left ventricular systolic and diastolic regional function after enhanced external counter pulsation therapy using strain rate imaging

Abstract: EECP therapy seemed to improve both regional and global LV systolic and diastolic functions in patients with chronic angina pectoris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
0
12
1
2
Order By: Relevance
“…Recently, it was reported that EECP therapy improved global LV systolic and diastolic functions in patients with chronic angina pectoris. There was a significant increase in LVEF with EECP treatment in the above mentioned study (29). In our study, EECP therapy resulted in a significant increase in post-EECP LVEF levels, a finding not evident in the control group.…”
Section: Discussioncontrasting
confidence: 50%
“…Recently, it was reported that EECP therapy improved global LV systolic and diastolic functions in patients with chronic angina pectoris. There was a significant increase in LVEF with EECP treatment in the above mentioned study (29). In our study, EECP therapy resulted in a significant increase in post-EECP LVEF levels, a finding not evident in the control group.…”
Section: Discussioncontrasting
confidence: 50%
“…[4][5][6][7][8] In 28 patients in New York Heart Association (NYHA) functional Class III and IV angina, EECP resulted in a significant improvements in left ventricular ejection fraction, and in both regional and global LV systolic function, as well as improved LV diastolic function. [6] In addition, in 24 patients with acute myocardial infarction and subsequent reperfusion therapy, Taguchi et al described an increase in preload with increased cardiac index, due to increased venous return following treatment with an EECP protocol. [7] Furthermore, Werner et al demonstrated that EECP led to improved mean arterial blood pressure, increased renal vascular resistance, as well as improved urinary flow rates, in 19 patients with liver cirrhosis, when compared with 12 healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Enhanced external counterpulsation (EECP) is increasingly being utilized by Cardiology Services around the world as an adjunct to the long-term management of chronic congestive heart failure as well as in the management of otherwise refractory angina. [4][5][6][7][8] EECP works by mechanistically improving venous return, enhancing peripheral resistance and thereby leading to the augmentation of left ventricular function. [4][5][6][7][8] We therefore speculated that bilateral SCDs, which are commonly used for DVT prophylaxis, may serve as mini-EECP devices for dialysis patients, and could therefore reduce or prevent IDH by improving venous return, mobilizing edema fluid, raising systemic peripheral resistance, and enhancing cardiac reserve.…”
Section: Introductionmentioning
confidence: 99%
“…41 In 20 patients with severe angina ineligible for revascularization, an improvement in New York Heart Association angina class was associated with improvement in DSI (peak systolic strain), and systolic and diastolic myocardial and diastolic transmitral velocities with enhanced external counterpulsation. 42 …”
Section: Myocardial Infarctionmentioning
confidence: 99%